2014
DOI: 10.2217/fnl.14.6
|View full text |Cite
|
Sign up to set email alerts
|

Translating Cerebellar Purkinje Neuron Physiology To Progress In Dominantly Inherited Ataxia

Abstract: The cerebellum is an important structure for accurate control and timing of movement, and Purkinje neurons in the cerebellar cortex are key players in cerebellar motor control. Cerebellar dysfunction can result in ataxia, a disorder characterized by postural instability, gait disturbances and motor incoordination. Cerebellar ataxia is a symptom of a number of conditions, and the emerging evidence that Purkinje neuron dysfunction, in particular, abnormal Purkinje neuron repetitive firing, is a major driver of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
1
23
1
Order By: Relevance
“…Rescue of spontaneous firing rate deficits independent of excitability deficits appears to correlate best with rescue of motor deficits, which although not a canonical deficit in ASD, is a frequent comorbid finding ( Fournier et al, 2010 ; Ming et al, 2007 ; Mosconi et al, 2015 ). Association of motor deficits with spontaneous firing deficits, independent of excitability deficits, is consistent with previous studies ( Chopra and Shakkottai, 2014 ), while rescue of this specific electrophysiological phenotype supports a possible mechanism that mTOR-related regulation of specific ion channels ( Häusser et al, 2004 ; Raman and Bean, 1997 ) at specific developmental periods may be driving these observed effects. Studies further characterizing the molecular basis for these findings will be an important avenue of future study.…”
Section: Discussionsupporting
confidence: 90%
“…Rescue of spontaneous firing rate deficits independent of excitability deficits appears to correlate best with rescue of motor deficits, which although not a canonical deficit in ASD, is a frequent comorbid finding ( Fournier et al, 2010 ; Ming et al, 2007 ; Mosconi et al, 2015 ). Association of motor deficits with spontaneous firing deficits, independent of excitability deficits, is consistent with previous studies ( Chopra and Shakkottai, 2014 ), while rescue of this specific electrophysiological phenotype supports a possible mechanism that mTOR-related regulation of specific ion channels ( Häusser et al, 2004 ; Raman and Bean, 1997 ) at specific developmental periods may be driving these observed effects. Studies further characterizing the molecular basis for these findings will be an important avenue of future study.…”
Section: Discussionsupporting
confidence: 90%
“…Impaired cognitive performance, involving language, executive, visuospatial and sequencing functions has also been found in patients with cerebellar atrophy [4][5], a condition characterized by diffuse degeneration of the cerebellar cortex, which is regarded as the central computational integrator of the cerebellar system [6]. Throughout the cerebellar cortex, the information ultimately converges on Purkinje neurons and is then funneled out through the neurons of the deep cerebellar nuclei (DCN), the sole output of the cerebellar cortex.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellar Purkinje neurons are able to support autonomous spiking in the absence of synaptic input, a property which depends crucially on appropriate function of a number of potassium (K + ) channels [ 8 10 ]. Much is known about how perturbations in K + channels affect Purkinje neuron spiking [ 11 13 ], including a number of studies which have identified changes in K + channels that produce aberrant spiking in mouse models of cerebellar ataxia [ 14 17 ]. Notably, targeting K + channels involved in aberrant spiking slows Purkinje neuron degeneration in several ataxia models [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%